Ectopic Oral Tonsillar Tissue: A Case Series with Bilateral and Solitary Presentations and a Review of the Literature - Masashi Kimura; Toru Nagao; Terumi Saito; Saman Warnakulasuriya; Hiroyuki Ohto; Akihito Takahashi; Kanji Komaki; Yoshiyuki Naganawa (Case Reports in Dentistry)
An ectopic tonsil is defined as tonsillar tissue that develops in areas outside of the four major tonsil groups: the palatine, lingual, pharyngeal, and tubal tonsils. The occurrence of tonsillar tissue in the oral cavity in ectopic locations, its prevalence, and its developmental mechanisms that belong to its formation remain unclear. In this report, we describe a rare case of bilateral symmetric ectopic oral tonsillar tissue located at the ventral surface of the tongue along with two solitary cases arising from the floor of the mouth. The role of immune system and its aberrant response leading to ectopic deposits desires further studies. As an ectopic tonsil may simulate a benign soft tissue tumor, this case series highlights the importance of this entity in our clinical differential diagnosis of oral soft tissue masses.